Naphazoline eye drops for the treatment of Horner syndrome following radical thyroid cancer surgery: A case report - Zhuang Li; Yong Liu; Hang Yin; Jiatong Chen; Feng Zhu (Journal of International Medical Research)
Horner syndrome is a rare complication following thyroid surgery, typically presenting with ptosis, miosis, and ocular congestion. We report the case of a 30-year-old female diagnosed with papillary thyroid carcinoma who underwent left thyroid lobectomy, isthmectomy, and comprehensive left cervical lymph node dissection. On the first postoperative day, the patient developed left-sided ptosis, a constricted pupil, blurred vision, and conjunctival congestion, leading to a clinical diagnosis of Horner syndrome. Initial treatment with oral neurotrophic agents provided limited improvement, with persistent ocular symptoms. Four months postoperatively, the introduction of topical naphazoline eye drops resulted in marked improvement. Ptosis diminished, the palpebral fissure returned to normal, pupil sizes equalized, and conjunctival congestion resolved, with effects lasting approximately 2 h after each application. This case report summarizes the mechanisms of injury leading to Horner syndrome after thyroid surgery, highlighting the importance of understanding the anatomical relationship between the thyroid gland and the cervical sympathetic nerve trunk during thyroidectomy to minimize the risk of Horner syndrome. This case highlights the potential role of topical α 1 -adrenergic agonists in managing postoperative Horner syndrome and underscores the need for intraoperative nerve protection strategies.